Ta’līm al-Lugah al-‘Arabiyyah bimajāl Mahārah al-Qirā’ah wa al-Kitābah - Rizka Riyani Lutfiati; Fitri Wahyuni (Aphorisme: Journal of Arabic Language, Literature, and Education, 2021)
In studying language, vocabulary is the key to understand language lesson. It is similar in learning Arabic. The vocabulary is important. In learning Arabic, there four skills. They are listening, writing, reading, and speaking. All students should have a lot of vocabulary. The main purpose of this research are: (1) to describe the intensity of reading vocabulary of the second grade students at Arrisalah Islamic Boarding School, (2) to describe the writing skills of the second grade students at Arrisalah Islamic Boarding School, (3) to understand the effect of vocabulary reading intensity to improve the students’ writing skills. The quantitative research was used. The data were collected from the students and the boarding school’s information by using observation, questionnaires, test, and documentation. Meanwhile, to determine the relationship and the effect of vocabulary reading intensity on the students’ writing skills product moment correlation was used. From this research, it is known that the reading vocabulary intensity is at a moderate level with a percentage result 64.70% and the writing skills are also at a moderate level with a percentage result 52.94%. By calculating the product moment correlation between reading vocabulary intensity and writing skills, it was found that the correlation number was 0.784 and the coefficient of determination in variable of the vocabulary reading intensity affects the students’ writing skills was 63%.